Unlocking e-wallet adoption: exploring the influence of functional barriers from a generation X perspective / Mohamad Amirul Rashid Mohd Yusof ... [et al.] - Mohd Yusof, Mohamad Amirul Rashid; Ismail, Mohd Noor Ismawi; Mazlan, Nurfatihah; Abd Aziz, Azdel; Mohd Aslin, Mohd Asyraf (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
Cashless systems play a crucial role in contemporary society as they facilitate the streamlining of financial transactions within the context of an increasingly interconnected world. In contemporary society, individuals tend to prefer utilizing cashless payment methods when doing their financial activities. The use of cellphones for conducting transactions gives a high level of convenience and requires minimal effort. Despite the emergence of Malaysia as a demonetizing economy, the adoption of e-wallets continues to face challenges, as there has been a limited reaction from customers. This study employed Innovation Resistance Theory, which encompasses the dimensions of usage, value, and risk, to investigate the factors that hinder the intention to use e-wallets among Generation X in Malaysia. Convenient sampling will be employed in this investigation, with the inclusion of screening components in the instrument to ascertain suitable respondents. A total of 128 respondents will be involved in this study, utilizing both online surveys through Google Form and hardcopy surveys among individuals belonging to Generation X in the Klang Valley region. The intended results of this study are anticipated to offer valuable insights to multiple stakeholders, including e-wallet service providers, business professionals, government entities, and Bank Negara Malaysia. These findings will enhance their comprehension of the barriers that hinder consumers from utilizing e-wallets. Consequently, this knowledge will assist in mitigating the resistance factors associated with e-wallet adoption, thereby promoting its acceptance and usage to a more favorable extent Hence, conducting a comprehensive inquiry on the barriers of resistance towards e-wallet adoption in Malaysia will be a compelling and valuable subject.